Quranic Narratives Addressing Atheism and the Rejection of God in Western Philosophy - Zubaidi, Sujiat; Sahidin, Amir; Armayanto, Harda; Binte Mochamad Sandisi, Zahratur Rofiqah (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2025)
Modern materialistic perspectives, combined with Western philosophical critiques that reject the existence of God, have contributed to the rise of atheistic worldviews. In response to this condition, this study aims to identify forms of atheistic rejection in Western philosophy, analyze Quranic thematic narratives related to faith and divine existence, and integrate both findings to demonstrate how the Qur’an addresses and counters atheistic thought. Using a qualitative literature-based method that employs Quranic thematic analysis and comparative philosophical analysis with references to classical and contemporary interpretations, this research finds that atheistic views reflected in the Qur’an include denial of the afterlife, moral accountability, religion, prophets, and the existence of God. The Qur’an counters these views through narratives on the purpose of life, the reality of the hereafter, divine justice, revelation, and prophetic guidance. This study contributes by offering a structured analytical framework that bridges Quranic epistemology and Western atheistic critique, highlighting the intellectual relevance of the Qur’an in addressing contemporary atheism